Effect of an Anionic Surfactant on the Kinetics of Base Catalysed Iodination of Acetophenones - Jena, Bidyadhar; Panigrahi, A.K.; Sinha, B.K (Asian Journal of Chemistry, 2010)
Kinetics of iodination of acetophenone by molecular iodine have been studied in varying composition of methanol-water mixture at different acidic pH maintained by acetic acid and sodium acetate buffer within a temperature range of 25–40ºC in presence of sodium lauryl sulphate (NaLS) of different concentrations. The product of the reaction has been analysed. The thermodynamic quantities for the reaction have been computed and discussed.